ChemInform Abstract: A One Pot, Metal‐Free, Three‐Component Domino Sequence for the Synthesis of Furans: An Efficient C—O and C—N Bond Formation Approach. Issue 35 (August 2016) - Guo, Pengfeng; Wang, Changcheng; Chen, Ya; Ou, Caijun; Jiang, Hangqi; Chen, Weifeng; Chen, Weixin; Cao, Hua
Abstract: The products are not obtained when aniline or piperidine is used as starting material.